2021
DOI: 10.1002/cjce.24279
|View full text |Cite
|
Sign up to set email alerts
|

Bubble behaviour investigation in a wet fluidized bed using digital image analysis

Abstract: Due to the presence of liquid bridge forces, wet particles reveal totally different fluidization behaviours than dry fluidized beds. This paper studies the bubble dynamics of wet Geldart‐D particles in a wet 2D fluidized bed. A digital image analysis method is adopted to identify bubbles and extract bubble properties based on MATLAB software. During fluidization, the bubble feature analysis of optimized binary images captures the bubble size variation, bubble fraction, and bubble shape. The results show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The time step, 0.001 s, specified in Table 3 is the maximum allowable in the simulation. The actual time step is limited by (11) where Δx cell is the cell dimension, u is the fluid velocity, and Δt is the time step in the flow direction. In order to maintain stability, accuracy, and speed of the calculation, the VR automatically adjusts the time step to keep the CFL number between 0.8 and 1.5 as specified in this study.…”
Section: Computational Particle Fluid Dynamics Model In the Barracuda...mentioning
confidence: 99%
See 1 more Smart Citation
“…The time step, 0.001 s, specified in Table 3 is the maximum allowable in the simulation. The actual time step is limited by (11) where Δx cell is the cell dimension, u is the fluid velocity, and Δt is the time step in the flow direction. In order to maintain stability, accuracy, and speed of the calculation, the VR automatically adjusts the time step to keep the CFL number between 0.8 and 1.5 as specified in this study.…”
Section: Computational Particle Fluid Dynamics Model In the Barracuda...mentioning
confidence: 99%
“…Several studies have been carried out on the measurement of bubble properties in fluidized beds using both experimental and numerical techniques. For instance, nonintrusive experimental techniques such as electrical capacitance tomography (ECT) and digital image sensing are widely used to measure the bubble properties in fluidized beds without interfering with the fluid flow dynamic behavior. However, most of these works are devoted to measuring bubble dynamics in fluidized bed columns containing one type of particle. By contrast, gasification reactors usually come with a bed of solids containing mixtures of inert particles and active biomass particles of different size distributions.…”
Section: Introductionmentioning
confidence: 99%
“…By monitoring the incipient fluidization, it was found that liquid addition changes the fluidization of Geldart Group B particles, shifting the fluidization properties of particles to Group A and then to Group C. 9,[22][23][24] Thus, it can be speculated that the effect of liquid addition on bubble characteristic in wet fluidization would be similar to that of reducing particle size in dry-particle fluidization. Previous studies on the bubbling characteristics of wet fluidization reveals that as liquid content increases, the liquid-bridge force contributes to smaller, irregular bubbles with smaller aspect ratio 25 and lower bubble fraction and bubble flow rate. 14 These findings cannot support the promotion of the evolution of bubble characteristics shifting from Geldart Group B particles to Group A and then to Group C when liquid is added.…”
Section: Introductionmentioning
confidence: 97%